2023
DOI: 10.1172/jci.insight.164579
|View full text |Cite
|
Sign up to set email alerts
|

Full-length optic nerve regeneration in the absence of genetic manipulations

Abstract: The inability of mature retinal ganglion cells (RGCs) to regenerate axons after optic nerve injury can be partially reversed by manipulating cell-autonomous and/or -non-autonomous factors. Although manipulations of cell-non-autonomous factors could have higher translational potential than genetic manipulations of RGCs, they have generally produced lower levels of optic nerve regeneration. Here we report that preconditioning resulting from mild lens injury (conditioning LI, cLI) prior to optic nerve damage indu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…This phenomenon, called the conditioning lesion effect, is mediated by infiltrative monocytes that secrete oncomodulin and perhaps other factors [42,[46][47][48][49]. We now find that inflammatory conditioning also has profound effects on optic nerve regeneration [50]. As noted earlier, either lens injury or zymosan at the time of optic nerve crush leads to moderate levels of optic nerve regeneration.…”
Section: A Conditioning Effect In Optic Nerve Regenerationsupporting
confidence: 70%
See 2 more Smart Citations
“…This phenomenon, called the conditioning lesion effect, is mediated by infiltrative monocytes that secrete oncomodulin and perhaps other factors [42,[46][47][48][49]. We now find that inflammatory conditioning also has profound effects on optic nerve regeneration [50]. As noted earlier, either lens injury or zymosan at the time of optic nerve crush leads to moderate levels of optic nerve regeneration.…”
Section: A Conditioning Effect In Optic Nerve Regenerationsupporting
confidence: 70%
“…As noted earlier, either lens injury or zymosan at the time of optic nerve crush leads to moderate levels of optic nerve regeneration. However, if a mild injury restricted to the lens capsule is performed two weeks prior to optic nerve crush, the resulting level of regeneration is several-fold higher than seen with either zymosan or lens injury at the time of nerve crush (Figure 5), and zymosan delivery two weeks prior to optic nerve crush has no benefit [50]. Repeated episodes of lens injury pre-and post-optic nerve crush result in even greater levels of regeneration, enabling RGCs to regenerate axons the full length of the optic nerve and into the optic chiasm within 3-4 weeks [50].…”
Section: A Conditioning Effect In Optic Nerve Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, GA induced β-tubulin aggregation and inhibited zymosan-induced axonal elongation even in vivo. Benowitz et al reported that zymosan induces macrophage invasion and appears to release trophic factors such as oncomodulin, stromal cell-derived factor 1, and CCL5 chemokine that can promote axonal elongation [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…DRG neurons, which survive axotomy and mount an effective regenerative response, respond to injury with a partial loss of transcripts that distinguish subtypes and the upregulation of numerous transcripts that support axon growth . RGCs are highly vulnerable to cell death and display limited spontaneous axon growth after axotomy but can be coaxed to regenerate long axons using a variety of interventions [20][21][22][23][24][25] . Accordingly, the transcriptional response of RGCs shows strong upregulation of transcripts associated with both cell death and axon regeneration.…”
Section: Introductionmentioning
confidence: 99%